BELIEFS-ATTITUDES AND JOB MOTIVATION PREDICTING DEVELOPMENTALLY APPROPRIATE VISUAL ARTS AMONG PRIVATE PRESCHOOL TEACHERS IN SELANGOR - Teng , Heng Lan; Hutagalung, Fonny Dameaty; Chew , Fong Peng (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Private preschool teachers played a vital role in implementing Developmentally Appropriate Practices (DAP), particularly in visual arts education, to support children’s cognitive, socio-emotional, and creative development. Despite the recognized importance of DAP in early childhood education, empirical evidence within the Malaysian context remained limited, particularly regarding how teachers’ beliefs-attitudes and job motivation influenced the implementation of DAP in visual arts among private preschool teachers. This gap limited understanding of the psychological factors that supported effective pedagogical practices in early childhood classrooms. Therefore, this study investigated the influence of teachers’ beliefs-attitudes and job motivation on their implementation of DAP in visual arts. A quantitative cross-sectional survey was conducted among 400 private preschool teachers in Selangor using a validated questionnaire and stratified two-stage random sampling. Multiple regression analysis revealed that teachers’ beliefs-attitudes significantly predicted job motivation (R² = 0.542), which in turn positively influenced the implementation of DAP in visual arts (R² = 0.532). Predictive validity analysis further supported the robustness of the proposed model. The findings indicated that teachers’ beliefs-attitudes and job motivation were significant predictors of DAP implementation, highlighting their important role in promoting effective developmentally appropriate visual arts practices in early childhood education. These results provided empirical evidence to support teacher professional development initiatives and policy strategies aimed at strengthening developmentally appropriate visual arts education in Malaysian private preschools.